Crossing borders in gender and culture - Gunesch, Konrad (Cambridge Scholars Publishing, 2018)
While gender issues are almost always multidimensional and complex, this book discusses them from a cultural angle and with a focus on crossing borders, to represent their concepts meaningfully and to illuminate their realities as sharply as possible. Its five parts detail specific aspects and issues within that focus, namely communication, literary representation, equality and violence, work and politics, and cross-cultural connections. This combination of a wide topical range with specific discussions of gender issues makes the volume's insights worthwhile for a wide range of readers, from i.